2020
DOI: 10.1186/s12879-020-05575-6
|View full text |Cite
|
Sign up to set email alerts
|

High incidence and persistence of hepatitis B virus infection in individuals receiving HIV care in KwaZulu-Natal, South Africa

Abstract: Background Hepatitis B virus (HBV), Human Immunodeficiency virus (HIV) and Tuberculosis (TB) are common infections in South Africa. We utilized the opportunity of care provision for HIV-TB co-infected patients to better understand the relationship between these coinfections, determine the magnitude of the problem, and identify risk factors for HBV infection in HIV infected patients with and without TB in KwaZulu-Natal, South Africa. Methods This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
3
21
3
Order By: Relevance
“…Similarly, a study conducted in Nigeria noted that sexually active adults with STIs are at high risk of acquiring Hepatitis B viral infections [17]. Agrawal et al and Govindan et al found a lower prevalence of HBV among patients infected with syphilis [18, 19], other studies have noted a high prevalence of syphilis, HIV, HCV and Hepatitis B co-infection [20, 21, 22, 23, 24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Nigeria noted that sexually active adults with STIs are at high risk of acquiring Hepatitis B viral infections [17]. Agrawal et al and Govindan et al found a lower prevalence of HBV among patients infected with syphilis [18, 19], other studies have noted a high prevalence of syphilis, HIV, HCV and Hepatitis B co-infection [20, 21, 22, 23, 24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on hepatitis B in the post-vaccination era have largely been conducted in health-care facilities or from tertiary healthcare facilities, with the majority of patients drawn from one or two provinces (Gauteng and KwaZulu Natal) or were among people living with HIV in care [16][17][18]. National sentinel studies reported HBsAg prevalence ranging from 2.9% in HIV-uninfected pregnant women in Western Cape in 2008 to 9.4% in HIV infected patients seeking treatment and care services in South Africa [9]. The national HBsAg test positivity rate declined annually, from 9.77% in 2015 to 8.09% in 2019, with a significant strong negative association over time [2].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in people receiving HIV care in South Africa found high incidence and persistence of HBV. The prevalence of hepatitis B surface antigen was 8.5% [95% confidence interval (CI): 7.7-9.3] at baseline and 9.4% (95% CI: 8.6-10.3%) at end of follow-up among people living with HIV [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although a history of TB was found to have 1.7-fold odds of association with persistent HBV viraemia at follow up, this was not statistically significant during multivariate analysis. In another South African large-cohort study, which studied factors associated with the incidence and persistence of HBV infection in patients receiving HIV care, a history of TB was found to be associated with a higher incidence of HBV infection [34].…”
Section: Discussionmentioning
confidence: 98%